A mutual coupled concentric crossed-Line split ring resonator (CCSRR) based epsilon negative (ENG) metamaterial for Tri-band microwave applications - Shahidul Islam M.; Islam M.T.; Mohd Sahar N.; Rmili H.; Amin N.; Chowdhury M.E.H. (Elsevier B.V., 2023)
A metamaterial design and its analysis based on an epsilon negative concentric crossed-line split ring resonator (CCSRR) have been presented in this paper. The CCSRR unit cell structure is the amendment of the typical concentric split ring resonator (CSRR). The inserted crossed line increases the electrical length of the presented CCSRR unit cell. The dimension of the proposed CCSRR unit cell is 10 10 1.575 mm3 and it is printed on the Rogers RT 5880 substrate material. The transmission frequency ranges from 6.33 GHz to 6.65 GHz, 10.42 GHz to 10.73 GHz, and 13.21 GHz to 13.42 GHz which covers the frequency bands of C, X, and Ku-band of microwave applications. A complete analysis of scattering parameters, effective medium parameters, mutual coupling effect as well as the unit cell characteristics with electromagnetic analysis have been performed in this study. The proposed CCSRR unit cell structure exhibits epsilon negative characteristics in the frequency ranges of 6.53 GHz to 6.96 GHz, 10.63 GHz to 10.91 GHz, and 13.37 GHz to 13.40 GHz. Experimental validation has also been performed by measuring the scattering parameters of the proposed CCSRR unit cell and its array structure. Furthermore, the capacitive coupling among the concentric split ring resonators within the 1 2 and 2 2 array structures have been studied which is based on the near field split gaps that lead to the fundamental inductive-capacitive resonances. Besides, the effective medium ratio 4.5 implies the effectiveness and compactness of the proposed CCSRR unit cell structure. The compactness, effective medium parameters, and effective medium ratio make the proposed CCSRR metamaterial appropriate for the microwave applications. 2020 The Author(s)